STUDY CORRELATION BETWEEN BURDEN AND QUALITY OF LIFE OF DEPENDENT ELDERLY CAREGIVERS IN KLITREN, YOGYAKARTA - Kristina, Hana; Widagdo, The MM; Perdamaian, Teguh K (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: Elderly with disabilities need caregiverâ€™s assistance in their activities of dailyliving. The caregiver can experience a burden during caring for dependent elderly. The burdenÂ can affect the caregiverâ€™s quality of life. Purpose: To measure and test the correlation between dependent elderlyâ€™s caregiver burdenand quality of life in Klitren Kampong, Gondokusuman District, Yogyakarta Municipality.Method: The subjects were primary informal caregivers aged â‰¥ 18 years with an excellent cognitive function caring for the elders with an ADL score <12. Respondents were selected using the consecutive sampling technique. This is quantitative research with a cross-sectional study design. Zarit Burden Interview and Caregiver Reaction Assessment were used to assessing the caregiverâ€™s burden. WHO Quality of Life-BREF was used to assess caregiverâ€™s quality of life. Data were analyzed using spearmanâ€™s rank correlation.Results: There were 21 female study subjects. The caregivers ' burden tended to be low inÂ each of the CRA and ZBI domains (mean=8.63Â±10.730â€“72.42Â±10.983). Caregiversâ€™ quality of life tended to be low (mean=49.76Â±11.962â€“60.76Â±11.726). There was a strong and statistically significant correlation between the impact on finance (p=0.000, Ï=-0.678) and the impact on health (p=0.002, Ï=-0.602) on CRA with the environmental domain of WHOQoLBREF. There was a strong and statistically significant correlation between the impact ofÂ  the schedule domain on CRA with the psychological domain of WHOQoL-BREF (p=0,000, Ï=0.683). Conclusion: There are significant correlations between caregiversâ€™ burden and quality of life, especially in specific domains. Caregivers with a higher burden have a lower quality of life.Â